Management Practices of the Integrated Organic Farming System in Gunungkidul District, Indonesia - S. Triyanto, Aris Slamet Widodo (2006)
An integrated organic farming system applies the concept of "Low External Input Sustainable Agriculture" (LEISA) and this system develops the livestock business and the crop business in one location or area using local resources to optimize inputs. This study is an attempt to analyze the management and economic characteristics of the integrated organic faming system in the Gunungkidul, Indonesia. The specific objectives of this study were: (i) to examine the socio-economic profile of farmers that practiced the integrated organic farming system, (ii) to evaluate the farm management practices, (iii) to determine the optimal allocation resources used in the integrated organic farming system. The study comprises three components. The first was a study on the social economic profile of the respondents. The second was a study on the farmers' management capability, based on the management functions of setting objectives, planning, controlling and decision-making. The third was a study on the optimal allocation of resources used in the integrated organic farming system. The Likert Scale was used to measure the fanners' management capability. The Linear Programming method was used to determine the optimal allocation of resources. Descriptive analysis was also used to explain the integrated organic fanning system that had been practiced in the study area. Primary data were collected from a fann survey and secondary data were obtained from relevant agencies. The study found that the integrated organic fanning system practiced is combination between integrated fanning and organic farming. Organic fertilizers and bio pesticides were the organic materials always used in the farming practice. The fanners made a special bio pesticide from local materials. The Gunungkidul fanners had applied the rotation system based on seasons in their farming practice. Paddy was planted in the rainy season, corn and peanut in the flfSt dry season and in the second dry season, the farmers planted watermelons and inter cropped between com and peanut. In the study area, the supply of organic fertilizer was from chickens, goats and cows. The supply of livestock fodder was from crop waste especially from paddy straw. Grass was also fed to cows and goats, especially to cows. Farmers also gave mineral concentrates that contained corn, waste from tofu and rice siftings. The results of the analysis on management capability show that the farmers had a low level of management capability in setting objective and controlling but they had a middle level of management capability in planning and decision-making.